Seroconversion and dynamics of IgG anti-SARS-CoV-2 antibodies during the pandemic: A two-month observation cohort study on the population of Sleman in Indonesia - Jajah Fachiroh; Septi Kurnia Lestari; Dewi Kartikawati Paramita; Bagas Suryo Bintoro; Fatwa Sari Tetra Dewi; Lutfan Lazuardi; Cici Permata Rusadi; Erti Nur Sagenah; Eggi Arguni (PLoS ONE, 2025)
Background This study describes the seroconversion and serodynamics of IgG antibodies against the RBD of SARS-CoV-2 in the general population of Sleman District, Yogyakarta Special Province. We aim to identify possible factors that correlate with the seroconversion and serodynamics of IgG antibodies against the RBD of SARS-CoV-2. Methods We performed a longitudinal study of the population at Health and Demographic Surveillance System (HDSS) Sleman, Yogyakarta, Indonesia. Study subjects were recruited between April and December 2021 using convenience sampling and were followed up 2 times, i.e. 4–5 and 8–9 weeks. The inclusion criteria for subjects were age ≥ 18 years, absence of flu-like symptoms, and negative COVID-19 by using GeNose C19® screening. A community-based survey on demographics, comorbidities and smoking habits were documented at baseline, while a history of vaccination, COVID-19-related symptoms, mobility, and preventive measures, weight and height as well as a venous blood draw, were collected at each visit. The anti-RBD-SARS-CoV-2 IgG antibody concentration from blood plasma was measured using chemiluminescent microplate immunoassay (CMIA). Descriptive analysis was performed based on IgG seropositivity by using chi-squared test or Fisher’s exact test, as appropriate. Logistic regression was subsequently performed to identify factors that were correlated with IgG seropositivity. Further, a grouping of subjects based on IgG seropositivity was done to analyze factors that might correlate with seroconversion and serodynamics of anti-RBD-SARS-CoV-2 IgG antibody. A P value ≤ 0.05 was considered to indicate a significant difference. Results Three hundred eighty-five (385) participants were analyzed. At baseline, 307 out of 385 (79.7%) subjects were seropositive for the IgG antibody against the RBD of SARS-CoV-2. Descriptive analysis showed that sex, marital status, smoking habits, obesity, vaccination status, and preventive measures were different between the IgG anti-RBD-SARS-CoV-2 seropositive and negative individuals (p≤ 0.05). Further analysis showed that, vaccination was the factor most strongly correlated with seropositivity [OR = 20.58; 95% CI 10.82, 39.15]. Based on the correlation, we separated subjects into 4 groups. Group 1 (seronegative-unvaccinated individuals; 50 subjects); Group 2 (seronegative-vaccinated individuals; 27 subjects); Group 3 (seropositive-unvaccinated individuals; 25 subjects); and Group 4 (seropositive-vaccinated individuals; 282 subjects). During monitoring, 27/49 (55.10%), 5/25 (20%), 9/22 (40.91%), and 27/257 (10.51%) of subjects in Group 1, 2, 3, and 4 respectively, received 1 or 2 doses of COVID19 vaccine. When comparing seroconversion at baseline and monitoring 2, positive IgG seroconversion was observed in Group 1 (from 0/51 (0%) to 23/49 (46.94%)) and Group 2 (from 0/27 (0%) to 10/25 (40%)), but negative seroconversion was observed in Group 4 (from 282/0 (100%) to 248/257 (96.50%)); while, all subjects in Group 3 remained seropositive at the end of monitoring. This evidence suggested for hybrid immunity, on which infection and vaccine simultaneously contributes to anti-RBD-SARS-CoV-2 IgG seroconversion. Conclusions A high seroprevalence of the IgG antibody against RBD-SARS-CoV-2 in the Sleman population was found to correlate with COVID-19 vaccination and as infection occurred, thus enhancing hybrid immunity. We also identified nonresponder and rapid antibody decaying individuals, that call for targeted vaccinations in addition to annual universal boosting.